Ethnomathematics: Exploring Lamban Pesagi to Instill the Concept of Plane Figures - Pratama, Elvandri Yogi; Dahlan, Jarnawi Afgani; Turmudi, Turmudi (Universitas Teknokrat Indonesia, 2025)
One of the interesting applications of ethnomathematics is utilizing traditional houses as learning media, particularly for understanding the concept of plane shapes, which forms a crucial foundation in geometry and various real-world applications. Lamban Pesagi, the traditional house of Lampung people can be used as a source or material in conveying geometry concepts. The research aims to discuss how Lamban Pesagi can be utilized as a medium for learning the concept of flat figures. This research examines the elements of mathematics (ethnomathematics) in the architecture of Lampung traditional houses, especially Lamban Pesagi, which is in the State Museum of Lampung Province. This research analyzes the geometry figures found in Lamban Pesagi and develops creative and innovative mathematics learning activities based on the analysis with the principles of constructivism. In addition, it can also evaluate the impact on students' understanding and attitudes through geometry ability tests, observations of student participation in learning activities, and questionnaires to measure students' attitudes towards mathematics. Based on the results of exploration and discussion, it can be concluded that in Lampung traditional houses, especially Lamban Pesagi, geometric shapes are found. The geometry shapes are in the form of flat figures including square, rectangle, parallelogram, rhombus and triangle. Lamban Pesagi with its various geometric shapes can be an interesting learning resource to teach the concept of plane figures. Students are invited to identify and categorize the figures, thus fostering pride in local culture and increasing motivation and understanding of geometry. The impact of this learning can be evaluated through comprehension test and questionnare to measure students’ attitudes.